Treatment of locally aggressive benign bone tumors by means of extended intralesional curettage without chemical adjuvants - EROL, BÜLENT (My University, 2022)
bone tumors treated with extended intralesional curettage without the use of adjuvant in a tertiary orthopedic oncology center. Method: A total of 172 patients treated with surgical curettage and high-speed burrs for the diagnosis of aneurysmal bone cyst, giant cell tumor, osteoblastoma, chondroblastoma, and chondromyxoid fibroma were included in the study. Demographic, radiological, and clinical data of the patients were analyzed. Results: One-hundred seventy two patients (101 (59%) female and 71 (41%) male) with a mean age of 23years (6–84). The mean follow-up period was 48months (18–108). In the study, a total of 8 (4.6%) patients had postoperative complications, 17 (9.9%) patients had recurrence in the postoperative period. Diameter greater than 5 cm was found to be a risk factor for recurrence (p<0.004). The probability of developing complications was found to be significantly higher in patients with recurrence (p<0.001). There was no significant relationship between recurrence and age, tumor type, and tumor stage. Conclusion: Successful treatment results can be obtained with extended surgical curettage, high-speed burr, and cauterization without the use of chemical adjuvants in locally aggressive bone tumors.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Treatment; local aggressive; bone tumor; curettage; recurrence; GIANT-CELL TUMOR; SURGICAL-TREATMENT; CRYOSURGERY; Treatment; local aggressive; bone tumor; curettage; recurrence